Haematological Responses to Ethanol Extracts of Chia Seed and Tiger Nut in Alloxan-Induced Diabetic Rats - Chinyere S. Nwaka; Andrew C. Nwaka (Journal of Tropical Medicine and Public Health Solutions, 2026)
Diabetes mellitus is often accompanied by disturbances in haematological indices, reflecting the broader metabolic stress of chronic hyperglycaemia. This study evaluated the effect of ethanol extracts of chia seed (Salvia hispanica) and tiger nut (Cyperus esculentus), administered separately and in combination, on haemoglobin (Hb), packed cell volume (PCV), red blood cell (RBC) count, white blood cell (WBC) count, lymphocyte, and neutrophil levels in alloxan-induced diabetic Wistar rats. Sixty-three male rats were assigned to nine groups of seven: normal control (A), diabetic untreated (B), diabetic + 100 mg/kg metformin (C), diabetic + 150 or 300 mg/kg chia extract (D, E), diabetic + 150 or 300 mg/kg tiger nut extract (F, G), and diabetic + 150 or 300 mg/kg combined extract (H, I), dosed orally once daily for 21 days after alloxan-induced diabetes was confirmed. At the end of treatment, Hb, PCV, and RBC were significantly higher (p